The effect of pile installation method on dynamic pile response. Issue 3 (1st September 2011) - Madabhushi, Gopal; Stringer, Mark
Abstract : The widespread use of piled foundations in areas prone to liquefaction has led to significant research being carried out to understand their behaviour during earthquakes. A key challenge in modelling this problem in a centrifuge is the installation procedure, and in most dynamic centrifuge experiments piles are installed before the test commences, either pushing the piles at 1 g, or fixing the piles in the model and the sand poured around them. In this paper, a series of dynamic centrifuge experiments are described in which a 2 × 2 pile group is pushed into the model before the test begins and also once the centrifuge has reached the test acceleration. The paper focuses on the key differences which were observed in the pile group's response to the earthquake motion, and in particular, the very different settlement responses of the pile groups.